2-Degenerate rectifying curves in M41 and their characterizations - Küçükarslan, Zühal; Öztekin, Handan; Bektaş, Mehmet (My University, 2011)
In the differential geometry of M41, it is well known that a 2-degenerate curve is a special s-degenerate curve in M41. In the light of this, in this work; we adapt notion of rectifying curves to 2-degenerate curves in M41 and characterize 2-degenerate rectifying curves with respect to their curvature functions. © 2010 Institute of Advanced Scientific Research.
Keywords: 2-degenerate curves; Lorentzian space; Rectifying curves; S-Degenerate Curves